Respuestas
Respuesta dada por:
3
Respuesta: −(−12)+6−(5+4−9−6+2−7)−6−5+8−4+1−2−7−2
=12
Explicación paso a paso:
−(−12)+6−(5+4−9−6+2−7)−6−5+8−4+1−2−7−2
=12+6−(5+4−9−6+2−7)−6−5+8−4+1−2−7−2
=18−(5+4−9−6+2−7)−6−5+8−4+1−2−7−2
=18−(9−9−6+2−7)−6−5+8−4+1−2−7−2
=18−(0−6+2−7)−6−5+8−4+1−2−7−2
=18−(−6+2−7)−6−5+8−4+1−2−7−2
=18−(−4−7)−6−5+8−4+1−2−7−2
=18−(−11)−6−5+8−4+1−2−7−2
=29−6−5+8−4+1−2−7−2
=23−5+8−4+1−2−7−2
=23+3−4+1−2−7−2
=23+−1+1−2−7−2
=23+0−2−7−2
=23+−2−7−2
=23+−9−2
=14−2
=12
Preguntas similares
hace 5 años
hace 8 años
hace 8 años
hace 9 años